CHARACTERISTIC PELLET OF HYDROTHERMAL TREATMENT OF EMPTY FRUIT BUNCH WITH HIGH ASH CONTENT FOR SOLID FUEL - Ahda, Yusuf
A large production of palm oil, always followed by the amount of solid waste products. Empty Fruit Bunch (EFB) are avoided as a solid fuel for boiler due to their physical characteristic such as very bulky, high moisture and potassium content. The hydrothermal treatment (HT) has been conducted in our research to overcome those problems. Objection of this study are analyze the temperature effect of HT to improve fuel properties of EFB for co-firing and getting high potassium content in liquid. One hundred grams of EFB and water with a L/S ratio of 5:1 mL/g was loaded into 2.3 L reactor. Temperature was varied from 120ºC, 150ºC, 180ºC, 200ºC, and 220ºC with holding time of 60 minutes. HT product was filtrated to separate solid (biochar) and liquid. The EFB sample, solid and liquid product of HT were analyzed to know their characteristic. The EFB and biochar was used as a feedstock for pellet production. 0.4 g of sample was loaded into 1 cm diameters pellet mold. Pellet’s production was operated at 200 and 200 bar. EFB dan biochar pellet was analyzed the strenght test. The results indicated that the properties on solid products could be improved by HT such as higher heating value is 21.81 MJ/kg at 220ºC compared with feedstock 19.68 MJ/kg. The lowest O/C ratio gathered at 220ºC is 0.61 compared with the feedstock 1.02. The H/C atomic ratios are 1.1 and 1.2 compared with the feedstock 1.4. The K2O content in char at 220ºC is 9.24% compared with feedstock 17.09%. Fouling and slagging index included in light categgory. Result of this research are HT could improve the fuel properties of EFB to biochar for co-firing fuel, HT lower fouling and slagging index, and EFB and biochar pellet meet the SNI standart requirement of wood pellet except the ash content.